IN VITRO ANTIOXIDANT AND ANTIVENOM ACTIVITIES OF AQUEOUS AND CHITOSAN-ENCAPSULATED TAMARINDUS INDICA SEED EXTRACTS AGAINST NAJA NIGRICOLLIS VENOM - Ibrahim, Yunusa Olatunji; Abdullahi, Abdulkadir; Muhammad, Fatima Madaki; Umar, Maimuna Bello; Abdulsalam, Halimat; Odu, 1Maureen; Ndamitso, Muhammad; Busari, Musa Bola (FUDMA Journal of Sciences, 2025)
Snake envenomation is a neglected tropical disease responsible for thousands of mortalities and morbidities annually. Naja nigricollis is one of the venomous snakes of most importance in Nigeria. The enzymatic component of its venom has been associated with devastating complications following envenomation. Hence, this study aimed to evaluate the in vitro antioxidant and antivenom activities of aqueous crude extract and chitosan-encapsulated extract of Tamarindus indica seed. In vitro antioxidant assays; DPPH radical and ferric reducing power assays as well in vitro antivenom activities; phospholipase A2 and proteinases inhibition assays were determined using standard methods. The extracts showed significant DPPH radical-scavenging activities and ferric-reducing powers. However, the encapsulated extract exhibited higher activities with IC50 values of 19.62 µg/mL and 3.67 µg/mL against DPPH radical and FRAP, respectively than crude extract with IC50 values of 33.27 µg/mL and 17.56 µg/mL, respectively. Further, the extracts exerted significant inhibitory effects against the venom enzymes, with the encapsulated extract showing higher inhibitory effects. The IC50 values of the encapsulated extract against the enzymes were 34.58 µg/mL and 45.53 µg/mL against phospholipase A2 and proteinases, respectively, while free extract had IC50 values of 47.42 µg/mL and 62.01 µg/mL, respectively. This is the first study evaluating antivenom potential of chitosan-encapsulated T. indica seed against N. nigricollis. The encapsulated extract showed potential antivenom activities and could serve as a drug lead for the production of herbal therapy against Naja nigricollis venom in order to address antivenom limitations.
Keywords: Naja nigricollis; Tamarindus indica; Snake venom; Antioxidant; Phospholipase A2; Proteinases; Chitosan nanoparticles